The association between the DNAH11 rs10248618 SNP and serum lipid traits, the risk of coronary artery disease, and ischemic stroke - Zhou, Yong-Gang (Int J Clin Exp Pathol, 2018)
Previous genome-wide association studies have shown that the rs10248618 single nucleotide polymorphism (SNP) in the dynein axonemal heavy chain 11 gene (DNAH11) has been associated with serum high-density lipoprotein cholesterol (HDL-C) levels. However, little is known about such association in the Chinese population. The present study was performed to clarify the association between the DNAH11 rs10248618 SNP and serum lipid traits and the risk of coronary artery disease (CAD) and ischemic stroke (IS) in the Guangxi Han population. Genotypes of the DNAH11 rs10248618 SNP in 1,213 unrelated patients (CAD, 600 and IS, 613) and 631 healthy controls were determined by snapshot technology. The genotypic and allelic frequencies of the SNP were significantly different between the CAD/IS patients and the controls (P < 0.01 for all). The CT/TT genotypes and the T allele were associated with an increased risk of CAD and IS (CAD: P < 0.01 for CT/TT vs. CC and T vs. C; IS: P < 0.01 for CT/TT vs. CC and T vs. C). The CT/TT genotypes in the healthy controls, but not in CAD or IS patients, were associated with a decreased serum HDL-C and apolipoprotein (Apo) A1 concentration. These results suggest that the DNAH11 rs10248618 SNP is associated with the risk of CAD and IS in our study population. It is likely to increase the risk of CAD and IS by reducing serum HDL-C and ApoA1 levels.